STUDY OF THE IMPACT OF VALUES ​​ON EDUCATIONAL ACHIEVEMENT OF SECONDARY LEVEL STUDENTS OF DELHI STATE - Ricky; Sharma, Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
To rescue parents from the state of neglect, such education is required which provides information about every aspect of life. It is the need of the present time that concrete efforts should be made at the national level towards parents, so that balanced development of all classes can be possible. The real meaning of making secondary level students competent is to make them progressive and civilized so that their reasoning power can be developed. Problem solving of the student is necessary for proper development, better adjustment, better life satisfaction and strength of his family. Values ​​are the main determinants of the behavior of any person. These are a part of the inner life of the person and are reflected by his behavior. Different types of values ​​like religious, ideological, natural etc. work as motivating force in the behaviour of a person. The principle of value cannot be defined specifically. Every person has his own experiences. Which keep on increasing with the change of time. Every person makes some rules or principles in his life on the basis of his conduct and experiences and they also become the philosophy of his life and remain with him throughout his life. These philosophies of life keep him constantly moving on the path of life and motivate him towards work.